Anthropogenic modifications in the erosional rhythm of a coastal cliff. Rocha do Gronho (western coast of Portugal) - Neves, M. (Journal of Iberian Geology, 2008)
The beach-cliff system “Rocha do Gronho” is a stretch of the west coast of Portugal that marks the southern limit of a coastal lagoon – The Obidos lagoon. The cliff is cut in sedimentary material and the elongated beach is generally narrow being almost submerged by the spring tides. Existing documents show that, in almost all of the second half of the twentieth century, there has been a state of equilibrium of the beach-cliff system because the abundance of sediments proceeding from the lagoon and carried south by the longshore current (predominantly N-S) provided a covering of the cliff base that protect it from the assailing force of the waves. The cliff face evolved mainly by small magnitude rockfall events. Between 1958 and 1995, a rate of retreat of 0.15m (±0.02m) year−1 was recorded. Afterwards, the frequency and the magnitude of the occurrences of mass movements had changed. Five events leading to a 33.6m retreat of the cliff top have been recorded. The type of movement, the affected length of the top of the cliff, the maximum retreat, the lost area of the top of the cliff and the volume of material displaced were estimated for each event. The identification of the processes involved as well as the evaluation of the potential triggering factors allowed an assessment of the influence of human intervention in the lagoon (changing the main draining paths and consequently the patterns of sediment transport) in the modifications of the “Rocha do Gronho” evolution.